(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The aim of the study is to determine the impact of applying Total Quality Management with its dimensions (employee participation, training, continuous improvement, senior management support, customer focus) on customer satisfaction in the application of Al Rajhi Cooperative Insurance Company. The study relied on the descriptive analytical approach, and the study sample amounted to (70) employees of Al Rajhi Cooperative Insurance Company, and (80) customers. The results of the study indicate that Total Quality Management (TQM) plays a crucial role in enhancing customer satisfaction in Al Rajhi Cooperative Insurance Company, as the results showed that the various dimensions of Total Quality Management, such as continuous improvement, training, senior management support, and customer focus, positively affect customer satisfaction. A clear statistical significance was observed for the contribution of these dimensions to improving the level of customer satisfaction, which enhances the effectiveness of applying Total Quality Management in achieving positive results in the company’s overall performance.